The Relationship Between Teachers’ Storytelling Skills and Children’s Listening Skills at TKA/TPA Al-Mujahidin Bawapitu, Pangkep Regency - Khatimah, Husnul (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to improve children’s listening skills through the storytelling method by utilizing the teacher’s storytelling ability at TKA/TPA Al-Mujahidin Bawapitu, Pangkep Regency. This research is a qualitative study. The subjects of this research were children and teachers at TKA/TPA Al-Mujahidin Bawapitu. The objects of the study were listening skills and teacher ability. The data collection methods used were observation and documentation conducted during the learning process. The data analysis technique applied in this study was descriptive quantitative analysis. The research was carried out over three meetings. The results of the study showed that children’s listening skills could be improved. The observation results indicated that in the first meeting, 3 children had good listening skills; in the second meeting, 12 children; and in the third meeting, the number increased to 17 children. Based on these results, it can be concluded that the storytelling method, supported by the teacher’s storytelling ability, can improve children’s listening skills. The process of improving listening skills through the storytelling method includes: (a) the teacher thoroughly preparing before storytelling, (b) the teacher selecting a storyline that is appropriate to the characteristics of children’s stories, and (c) the teacher giving rewards to children who are active while listening to the story.